2020
DOI: 10.1016/j.anr.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Low Body Mass Index for Early Screening of Adolescent Idiopathic Scoliosis: A Comparison Based on Standardized Body Mass Index Classifications

Abstract: Scoliosis is a common musculoskeletal problem in adolescents. This study aimed to identify the prevalence of adolescent idiopathic scoliosis (AIS) and its associated factors among Korean adolescents. The prevalence of thin individuals among students with AIS was compared based on body mass index (BMI) classifications. Methods: This study was a secondary data analysis and used the 2016 Korean National Health Examination for School Students data. Data from 16,412 students were analyzed using descriptive statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…Various possible risk factors related to the onset of scoliosis have been studied in the literature, such as growth alterations, postural disorders, heavy backpacks, environmental factors, high-risk sports and visual and dental disorders [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various possible risk factors related to the onset of scoliosis have been studied in the literature, such as growth alterations, postural disorders, heavy backpacks, environmental factors, high-risk sports and visual and dental disorders [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lower BMI prevails among AIS patients and has been reported previously [43]. Researches have reported the following possible reasons for lower BMI including leptin dysfunction, psychological factors [44 , 45]. However, the relationship between BMI and AIS is complex and the relevance of this relationship in terms of the pathogenesis of AIS remains unknown.…”
Section: Discussionmentioning
confidence: 87%
“…Low BMI is not only related to treatment and intervention, but also to scoliosis prevalence. KIM reported that the prevalence of thin students with scoliosis could increase by up to four times depending on the BMI criteria [29]. Jeon reported that low weight and the risk of developing scoliosis are very closely associated [30].…”
Section: Discussionmentioning
confidence: 99%